Angiotensin-Converting Enzyme 2: SARS-CoV-2 Receptor and Regulator of the Renin-Angiotensin System. Issue 10 (8th May 2020) - Gheblawi, Mahmoud; Wang, Kaiming; Viveiros, Anissa; Nguyen, Quynh; Zhong, Jiu-Chang; Turner, Anthony J.; Raizada, Mohan K.; Grant, Maria B.; Oudit, Gavin Y.
Abstract : ACE2 (angiotensin-converting enzyme 2) has a multiplicity of physiological roles that revolve around its trivalent function: a negative regulator of the renin-angiotensin system, facilitator of amino acid transport, and the severe acute respiratory syndrome-coronavirus (SARS-CoV) and SARS-CoV-2 receptor. ACE2 is widely expressed, including, in the lungs, cardiovascular system, gut, kidneys, central nervous system, and adipose tissue. ACE2 has recently been identified as the SARS-CoV-2 receptor, the infective agent responsible for coronavirus disease 2019, providing a critical link between immunity, inflammation, ACE2, and cardiovascular disease. Although sharing a close evolutionary relationship with SARS-CoV, the receptor-binding domain of SARS-CoV-2 differs in several key amino acid residues, allowing for stronger binding affinity with the human ACE2 receptor, which may account for the greater pathogenicity of SARS-CoV-2. The loss of ACE2 function following binding by SARS-CoV-2 is driven by endocytosis and activation of proteolytic cleavage and processing. The ACE2 system is a critical protective pathway against heart failure with reduced and preserved ejection fraction including, myocardial infarction and hypertension, and against lung disease and diabetes mellitus. The control of gut dysbiosis and vascular permeability by ACE2 has emerged as an essential mechanism of pulmonary hypertension and diabetic cardiovascular complications. Recombinant ACE2, gene-delivery of Ace2, Ang 1–7 analogs, and Mas receptor agonists enhance ACE2 action and serve as potential therapies for disease conditions associated with an activated renin-angiotensin system. rhACE2 (recombinant human ACE2) has completed clinical trials and efficiently lowered or increased plasma angiotensin II and angiotensin 1-7 levels, respectively. Our review summarizes the progress over the past 20 years, highlighting the critical role of ACE2 as the novel SARS-CoV-2 receptor and as the negative regulator of the renin-angiotensin system, together with implications for the coronavirus disease 2019 pandemic and associated cardiovascular diseases.